2019
DOI: 10.1021/acssuschemeng.9b03002
|View full text |Cite
|
Sign up to set email alerts
|

Ampholytic Chitosan/Alginate Composite Nanofibrous Membranes with Super Anti-Crude Oil-Fouling Behavior and Multifunctional Oil/Water Separation Properties

Abstract: Owning to its highly viscous and adhesive properties, viscous crude oil tends to easily adhere onto separation materials, resulting in serious fouling. Herein, we report an ampholytic nanofibrous membrane composed of a pair of oppositely charged biopolymerspositive chitosan (CS) and negative sodium alginate (ALG). CS and ALG were homogeneously complexed with each other to form a well-defined, interconnected, and entangled nanofibrous structure in a cosolvent of the LiOH/KOH/urea aqueous system after sequentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(21 citation statements)
references
References 45 publications
0
21
0
Order By: Relevance
“…On the other hand, membrane processes are considered a suitable and low-cost alternative to the conventional techniques for treatment of oilfield wastewater, due to unique properties such as the simples process, low energy consumption and no phase transformation [6,7]. Recent studies have reported the use of polymeric membranes for oily wastewater treatment [8][9][10]. Zhang, B. et al [11] reported the use of a polytetrafluoroethylene (PTFE) membrane for the study of the mechanisms of adsorption fouling of crude oil.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, membrane processes are considered a suitable and low-cost alternative to the conventional techniques for treatment of oilfield wastewater, due to unique properties such as the simples process, low energy consumption and no phase transformation [6,7]. Recent studies have reported the use of polymeric membranes for oily wastewater treatment [8][9][10]. Zhang, B. et al [11] reported the use of a polytetrafluoroethylene (PTFE) membrane for the study of the mechanisms of adsorption fouling of crude oil.…”
Section: Introductionmentioning
confidence: 99%
“…Until now, there have been fewer studies that consider these two kinds of pollution problems jointly. 8,9 Therefore, it is crucial to develop materials that can deal with the two types of water pollution problems simultaneously. 8−10 The oil−water separation materials reported in recent years can be mainly divided into block-shaped adsorbent materials and membrane-shaped filter materials.…”
Section: Introductionmentioning
confidence: 99%
“…It is of great practical significance to remove oil and heavy metal ions from water synchronously. , There is a great demand for materials to deal with oil–water emulsion and heavy metal ion pollution. Until now, there have been fewer studies that consider these two kinds of pollution problems jointly. , Therefore, it is crucial to develop materials that can deal with the two types of water pollution problems simultaneously. …”
Section: Introductionmentioning
confidence: 99%
“…Chitosan, a cationic polysaccharide composed of β-(1–4) linked 2-acetamido-2-deoxy-β- d -glucopyranose and 2-amino-2-deoxy-β- d -glycopyranose, is an alkaline deacetylation product of chitin, the second most abundant polysaccharide, which mainly comes from the exoskeletons of crustaceans, insects, beetles, as well as the cell walls of fungi [ 1 ]. Many of the applications of chitosan in several fields are based on its biological and excellent cationic properties [ 2 , 3 ], including biocompatibility [ 4 ], low immunogenicity, low or no toxicity, and antibacterial and moisture retentive properties [ 5 , 6 ]. Chitosan-based nanomaterials (such as nanogels, nanofibers, and nanocrystals) have been paid increasing attention due to their size-specific and free amine properties.…”
Section: Introductionmentioning
confidence: 99%